Management and prognosis of cancers in the accessory parotid gland - Han, Xiaoxue (J Int Med Res, 2018)
OBJECTIVE: This study was performed to analyze the clinical management of accessory parotid gland (APG) cancer and possible risk factors for disease-related death. METHODS: Patients diagnosed with primary APG cancers in the largest medical center in Northeast China were enrolled from January 1990 to December 2016. RESULTS: All 43 patients underwent resection of the tumors and superficial parotid gland by a standard Blair incision. Seven (16.3%) patients also required selective neck dissection. The most common lesion was mucoepidermoid carcinoma. Temporary facial paralysis occurred in 11 (25.6%) patients, and permanent facial paralysis occurred in 3 (7.0%) patients because of surgical resection of the facial nerve, which was involved with the tumor. The 5- and 10-year disease-specific survival rates were 86.0% and 66.0%, respectively. The tumor stage, neck status, neck dissection, and tumor grade were significantly associated with disease-related death, but only the tumor grade was an independent risk factor. CONCLUSION: Superficial parotidectomy is a reliable surgical procedure associated with a high survival rate and low morbidity in treating APG cancers. The tumor grade is the key prognostic factor.